Phase selective localization of silica filler in polymethyl methacrylate/ethylene vinyl acetate (PMMA/EVA) composites - Teoh, Pei Ying (School of Materials Engineering, 2019)
Silica content was varied from 0, 10 and 20 phr (approximately 9.1 weight % and 16.7 weight %, respectively). Melt blending was carried out by using a twin-screw extruder. PMMA/EVA/Si composites for each recipe were prepared in three different silica-dispersing methods. The first method was conventional compounding by addition of silica into melt PMMA/EVA blend (notated as CON). The second method was pre-dispersion of silica into PMMA phase (Si/M), which was further blended with extruded EVA to get the final composite (notated as Si/M-EVA). The third was pre-dispersion of silica into EVA phase (Si/E) and followed by blending Si/E with extruded PMMA to get the final composite (notated as Si/E-PMMA). For the case of PMMA dominion ratio - 70/30 PMMA/EVA/Si composites, pre-dispersion of Si into EVA was prepared by using a heated-two rolls mill so that 20 phr silica could be dispersed into 30 phr EVA. The Si/M and Si/E (pre-dispersed polymer) compound was pelletized for further melt blending process to get the final compounds.